Pengaruh Gaya Kepemimpinan Kepala Sekolah, Ketersediaan sumber daya pendidikan dan kualitas pembelajaran terhadap hasil belajar siswa dengan motivasi belajar sebagai variabel intervening - Gusmita, Neli; Elfiswandi, Elfiswandi; Veri, Jhon (Journal of Information System, Applied, Management, Accounting and Research, 2025)
This study aims to analyze the influence of Principal's Leadership Style, Student Engagement, and Curriculum on the Learning Environment and Learning Outcomes in schools. The sample used in this study consisted of 100 respondents, comprising teachers and students. Data were collected using a questionnaire and analyzed using SmartPLS to test the relationships among variables. The results of the study showed that: (1) there is a significant influence of Principal's Leadership Style on the Learning Environment; (2) there is a significant influence of Student Engagement on the Learning Environment; (3) there is a significant influence of Curriculum on the Learning Environment; (4) there is a significant influence of Principal's Leadership Style on Learning Outcomes; (5) there is a significant influence of Student Engagement on Learning Outcomes; (6) there is a significant influence of Curriculum on Learning Outcomes; (7) there is no significant influence of the Learning Environment on Learning Outcomes; (8) the Learning Environment does not mediate the relationship between Principal's Leadership Style and Learning Outcomes; (9) the Learning Environment does not mediate the relationship between Student Engagement and Learning Outcomes; and (10) the Learning Environment does not mediate the relationship between Curriculum and Learning Outcomes. These findings provide important contributions to educational management, particularly in the roles of school principals, student engagement, and curriculum implementation in creating an environment that supports optimal learning outcomes